Man in the Cosmos: Italo Calvino’s Cosmic Ecology in The Cosmicomics (ENTHYMEMA, 2024)
Italo Calvino’s The Cosmicomics, despite its pluralistic openness to multiple critical interpretations by various theoretical and conceptual frameworks including post-humanism, science-fiction studies, postmodernism and many more, deals with the fundamental issue of the human’s physical and conceptual inseparability from Nature or the cosmos. The human’s inseparability from the non-humans (including animals, vegetation and inanimate matters) has profound ecological implications. What Calvino establishes in the mentioned text is the human’s inevitable and unconditional inclusion in Nature rather than his self-proclaimed, physical/conceptual exclusion from the same. This is vindicated by the fictional illustrations in the text in which the ‘human’ is posited as a mere member of the ecosystem, and not as its master. In this context, this article endeavours to explore and analyze the said ecological implications of the mentioned work in the light of some the established ecological theories and postulations.
Keywords: Ecology; Human; Nature; Cosmos; Anti-anthropocentrism; Time; Space